PENINGKATAN PRODUKTIVITAS KERJA GURU MELALUI PENGEMBANGAN KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI - Atiyatu Jakiyah; Sumardi Sumardi; Rais Hidayat (JURNAL MANAJEMEN PENDIDIKAN, 2018)
This research applies quantitative research with correlational approach. This study outlines how the productivity of teachers work can be improved, by researching and seeking relationships between: 1) transformational leadership of principals with teacher work productivity, 2) organizational culture with teacher work productivity, 3) transformational leadership and organizational culture together equal to teacher work productivity. This research was conducted at private vocational school in Cibinong Sub-district, Bogor Regency in Year 2018. The number of population in this study is 240 with the number of samples of 150. Data were collected from a questionnaire with Rating Scale. The analysis technique uses partial regression and multiple correlation. The research finding points out three conclusions that is: first, there is positive and significant correlation between transformational leadership with teacher work productivity. Second, there is a positive and significant correlation between organizational culture with teacher work productivity. Third, There is a positive and significant relationship between transformational leadership and organizational culture together with teacher work productivity.Keywords: Transformational Leadership, Organizational Culture, Teacher Productivity